Given that f ( x ) = x − 1 1 and g ( x ) = x 2 − 3 x + 2 3 , find x → 1 lim g ( x ) f ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f(x)/g(x)=x^2-3x+2/3(x-1) x^2-3x+2=(x-1)(x-2) =>f(x)/g(x)=(x-1)(x-2)/3(x-1) =(x-2)/3 lim x->1 f(x)/g(x)=1/3 lim x->1 (x-2) =1/3*-1 =-1/3
First: x 2 − 3 x + 2 3 x − 1 1 = 3 x − 3 x 2 − 3 x + 2
Since x → 1 lim x 2 − 3 x + 2 = 0 ∧ x → 1 lim 3 x − 3 = 0 you can also use the L'Hôpitals rule to get x → 1 lim 3 x − 3 x 2 − 3 x + 2 = x → 1 lim 3 2 x − 3 = 3 − 1
Noob using l hopital rule....
That was so easy. Easy money easy life.
Not everyone will think it's easy mate. This is what we call bragging.
I did at 4 am in 20 sec at bed, only thinking
This is one of those factor, cancel, plug it in sort of limit problems. g(x) = (x-1)(x-2). Eliminate the common factor of (x-1) in f and g and we are left with (x-2)/3 no problem. Why can we "plug it in"? Because (x-2)/3 is defined, continuous at 1, and equal to f/g everywhere but 1.
It's too simple,☺😊.. however it's good to memorize.
Problem Loading...
Note Loading...
Set Loading...
For g ( x ) f ( x ) , we know that since both function is undefined at x = 1 , then we multiply the fraction with x − 1 x − 1 , which gives
g ( x ) f ( x ) = x − 2 3 1 = 3 x − 2 ⇒ x → 1 lim g ( x ) f ( x ) = − 3 1